Nutrient and Antinutrient Compositions and Heavy Metal Uptake and Accumulation in S. nigrum Cultivated on Different Soil Types - Adijat Funke Ogundola; Callistus Bvenura; Anthony Jide Afolayan (The Scientific World Journal)
Solanum nigrum cultivated on different soil texture types, sandy clay loam, silty clay loam, clay loam, loam, and control soils, were evaluated for proximate compositions, antinutrients, vitamins, and mineral composition with plant age using standard analytical methods. Accumulation of trace elements using translocation factor was studied to determine their toxic levels in plant tissues. Data were analysed by ANOVA and results expressed as means and standard deviation. Ash content, crude fibre, protein, alkaloid, phytate, and saponin ranged between 11.4 and 12%, 19.24 and 19.95%, 34.23 and 38.98, 42.08 and 45.76 mg/ml, 0.84 and 1.17%, and 94.10 and 97.00%, respectively. Vitamins A, C, and B were present in high quantity. Macro- and micronutrients recorded showed that S. nigrum is a potential reservoir of minerals. Accumulation of micronutrients was observed to be the highest at the flowering stage between the 4th and 5th weeks after transplanting. Plants cultivated on clay loam, silty clay loam, and loam soils accumulated elevated nutritional compositions and abundant antinutrients. However, the accumulated trace metals in the plants are within the recommended safe levels. All nutrient values are in the recommended requirements for daily consumption.